Effect of Bagging on Fruit Quality of Guava - Meena, Kamal Ram; Maji, Sutanu; Kumar, S.; Parihar, Dushyant; Meena, D. C. (International Journal of Bio-resource and Stress Management, 2023)
An investigation on improvement of quality of guava cv. Lalit fruits through bagging was carried out at Department Applied Plant Science, Babasaheb Bhimrao Ambedkar University, Lucknow, India during October 2012- March 2013. The area of experiment was dry and comes under subtropical area of central Uttar Pradesh. Various polyethylene covers with different colours i.e. silver, white, yellow, green, black and pink were included for the study and uncovered fruits were kept for the control. The results revealed that fruit bagging in general, improved the growth and quality development of guava fruits as compared to unbagging control. It was also observed that fruit size, weight and pulp content increased due to fruit covering. Fruit was found maximum in size under yellow polythene followed by white polythene while, black polythene showed maximum pulp percentage followed by green polythene. Fruit bagging also improved the fruit quality in terms of TSS, total sugars and TSS: acid ratio which were found maximum (14.25° Brix, 11.14% and 30.07, respectively) under yellow polythene but, maximum vitamin C (171.14 mg 100 g-1) content was recorded under white polythene. Among the various fruit covering materials bagging with yellow coloured polythene was found to be the best for overall improvement of physico-chemical quality of winter season guava cv. Lalit under subtropical climate of central Uttar Pradesh.